Necessary and Sufficient Conditions of Optimality for a Damped Hyperbolic Equation in One-Space Dimension - Kucuk, Ismail; Yildirim, Kenan (HINDAWI PUBLISHING CORPORATION, 2014)
The present paper deals with the necessary optimality condition for a class of distributed parameter systems in which the system is modeled in one-space dimension by a hyperbolic partial differential equation subject to the damping and mixed constraints on state and controls. Pontryagin maximum principle is derived to be a necessary condition for the controls of such systems to be optimal. With the aid of some convexity assumptions on the constraint functions, it is obtained that the maximum principle is also a sufficient condition for the optimality.
Keywords: WEAK MAXIMUM PRINCIPLE; STATE CONSTRAINTS; FEEDBACK CONTROLS; SYSTEMS; PROOF; DIFFERENTIABILITY; STABILIZATION; Mathematics